KEMAMPUAN MAHASISWA MENGAPLIKASIKAN KRITIK SASTRA MARXIS DALAM PENELITIAN SASTRA INTERDISIPLINER - Supsiadji, Rudi (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2009)
Abstract. This article is exploring student’s ability in applying Marxist theory. The discussion comes the conclusion that the s student’s ability in applying Marxist theories shows three tendencies: (1) there are limited research applying Marxist theories; (2) Out of various Marxist theories, Karl Marx’s opinions have become the most favourite to use; (3) Students’ abilities in comprehending and applying Marxist theories are far from expectation. Key waors: mastering theories, applying theories, socialist realism, Marxist criticism, conflict of class